1999
DOI: 10.1530/eje.0.1400224
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chronic treatment with GH on gonadal function in men with isolated GH deficiency

Abstract: Eleven adult males, previously submitted to neurosurgery because of a pituitary lesion (three with craniopharyngioma, three with clinically non-functioning adenoma and five with macroprolactinoma) were treated with recombinant GH for 12 months after the diagnosis of GH deficiency was made. Circulating FSH, LH, prolactin, testosterone, 17b-estradiol (E 2 ), dehyroepiandrosterone (DHEA-S), androstenedione, 17-OH-progesterone (17OHP), IGF-I, and steroid hormone-binding protein (SHBG) levels were assayed before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 34 publications
3
33
1
1
Order By: Relevance
“…In accordance with the results obtained by GHR genotyping, one clinical study found reduced semen volume in patients with untreated isolated GHD (4), whereas another study reported increased semen volume during GH replacement therapy (2). As concerns the Table 2 Associations between serum IGF1 and IGFBP3 vs semen quality.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…In accordance with the results obtained by GHR genotyping, one clinical study found reduced semen volume in patients with untreated isolated GHD (4), whereas another study reported increased semen volume during GH replacement therapy (2). As concerns the Table 2 Associations between serum IGF1 and IGFBP3 vs semen quality.…”
Section: Discussionsupporting
confidence: 69%
“…Reduced total sperm numbers have been reported in a group of patients with isolated GHD (4), whereas two other studies did not report any influence on spermatogenesis during GH replacement therapy (2,26). Experimental GH therapy has also been applied to infertile men without pituitary disease (27,28) or as adjuvant therapy during gonadotropin therapy of hypogonadotropic hypogonadism (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In einer aktuellen Studie konnte durch Gabe für die proteinogene α-Aminosäure L-Arginin eine gesteigerte Motilität nachgewiesen werden [89]. Positive Effekte zeigten die Gabe von rekombinantem Wachstumshormon (GH) bei isoliertem Hormonmangel [90] und im Tierversuch Lisinopril, einem Angiotensin-Converting-Enzyme-(ACE-)Hemmer [91]. Der Versuch, mittels einmaliger i. v.-Gabe von Oxytocin eine schwere Oligozoospermie zu verbessern, war erfolglos [92].…”
Section: Weitere Substanzenunclassified